Mindfulness for Teachers: Strategies to Manage Stress and Improve Learning Quality in Madrasah - Imam Gojali; Fathi Hidayah; Ana Aniati; Hasan Baharun (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This study focuses on the effectiveness of mindfulness training in reducing stress and improving the mental well-being of Islamic Religious Education (PAI) teachers at school. This study aims to examine the effectiveness of mindfulness training in reducing stress and improving the mental well-being of PAI teachers. The research method used is a qualitative approach with a descriptive type of research involving data collection techniques in the form of in-depth interviews, participatory observations, and document analysis. The results showed that mindfulness training significantly reduced stress and improved teachers' mental and emotional well-being, which positively impacted their interactions with students and the quality of teaching. This study implies that integrating mindfulness in teacher welfare management can be an effective strategy for improving the quality of education, especially in the context of Islamic education. This study also emphasises the importance of community support and a supportive learning environment in reinforcing the positive effects of mindfulness.